TECHNOLOGICAL PECULIARITIES IN RESPECT OF OBTAINING SEGMENT TEETH OF GRAIN AND FODDER HARVESTING MACHINERY SICKLES BY PLASTIC DEFORMATION - L. A. Isayevich; D. M. Ivanitsky; V. A. Korol (Наука и техника)
The paper presents a new technology for formation of segment teeth of agricultural machinery by plastic deformation instead of mechanical machining. Changes in segment design that permit to improve its operation and cutting quality are given in the paper. The paper describes advantages of the new technology allowing to ensure significant economical effect and increase sickle endurance and longevity. Power parameters of deformation process are theoretically calculated and justified by the experiments. The paper contains results of comparative sickle testings which have been manufactured in accordance with conventional new technologies.